Gambaran Self Transendence Mahasiswa Dengan Peran Ganda Pada Fase Quarter Life Crisis - Ummu Aimma Fiddina (CV. ITTC INDONESIA, 2026)
This study aims to explore the manifestation of self-transcendence during the quarter-life crisis phase. The phenomenon is grounded in the premise that the quarter-life crisis is a critical life stage requiring the role of self-transcendence. A quarter-life crisis is characterized by feelings of anxiety that emerge as individuals reach their mid-20s, encompassing fears regarding future prospects, career, relationships, and social life. This research employs a qualitative method with a phenomenological approach. Data were collected through observation and in-depth interviews with two female college students who are married and have children. The data analysis process involved stages of data collection, data reduction, data verification, data presentation, and conclusion drawing. The results indicate that both subjects exhibit self-transcendence. This is evidenced by the emergence of interpersonal, intrapersonal, and transpersonal aspects within the subjects. These aspects manifested with varying intensities of behavioral frequency in each subject. The findings of this study are expected to contribute to the development of psychological science in general, and specifically to educational and social psychology.